Induction of 1-FEH in Mature Chicory Roots Appears to be Related to Low Temperatures Rather than to Leaf Damage - W. Van den Ende; A. Van Laere (The Scientific World Journal, 2002)
Large-scale inulin production from chicory roots (Cichorium intybus L.) is hampered by the induction of 1-FEH activity (fructan 1-exohydrolase) and concomitant fructose production in autumn, coincident with a period with low night temperatures that cause leaf damage. To understand whether leaf damage per se is sufficient for 1-FEH induction and fructan breakdown, we defoliated mature chicory plants at a preharvest stage (September 10) and investigated the changes in carbohydrate levels and 1-FEH activities. Also, the activities of 1-SST (sucrose:sucrose 1-fructosyl transferase, EC 2.4.1.99), 1-FFT (fructan:fructan 1-fructosyl transferase, EC 2.4.1.100), and acid invertase (EC 3.2.1.26) were determined. Defoliation did not result in a prompt fructan breakdown and increase in 1-FEH activity, but after 10 days fructan breakdown and 1-FEH activities became higher in the defoliated plants. Defoliation resulted in a sharp decrease in 1-SST activity over the first 24 h. Afterwards, root 1-SST activities of defoliated plants remained at a lower level than in control plants. 1-FFT and invertase activities were not affected by defoliation. It can be concluded that defoliation of plants at the preharvest stage by itself did not induce the same rapid changes as observed in naturally induced October roots by low temperature (harvest stage). Taken together with our finding that 1-FEH is not induced in chicory roots when plants are transferred to the greenhouse early autumn (minimal temperature 14°C), we conclude that low temperatures might be essential for 1-FEH induction.